Leadership Styles Identification – Case of the Company from an Industrial Installations Sector - Czech, Olivia (Identyfikacja stylów przywództwa – przypadek firmy z branży instalacji przemysłowych, 2024)
The thesis focuses on the topic of leadership, including the definitions and characteristics of leadership and its styles. The study was aimed to diagnose the dominant leadership style in a medium-sized Polish company from the industrial installations sector. The research sample completed the survey related to Goleman’s leadership styles. Respondents used a 5-point Likert scale to evaluate the questions. The affiliative leadership style turned out to be the most dominant one in the organisation. The knowledge of the leaders’ behaviour was used to correlate the survey results with the actual state, and it turned out that the results reflect the actual frequency of using specific styles in the organisation. The results were also compared with other existing studies on leadership based on the six Goleman leadership styles, which allowed for noticing there is a style that was dominant or meaningful in each of these studies, and that is the affiliative style.
Czech, O. (2024). Leadership Styles Identification – Case of the Company from an Industrial Installations Sector. W J. Radomska & A. Witek-Crabb (Red.), New Trends in Business Management (s. 103–117). https://doi.org/10.15611/2024.30.7.08
Keywords: leadership; leadership styles; Goleman; przywództwo; style przywództwa